2018
DOI: 10.3324/haematol.2018.194282
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab plus lenalidomide and dexamethasone versus lenalidomide and dexamethasone in relapsed or refractory multiple myeloma: updated analysis of POLLUX

Abstract: In the POLLUX study, daratumumab plus lenalidomide/dexamethasone significantly reduced risk of progression/death versus lenalidomide/dexamethasone alone in relapsed/refractory multiple myeloma. We provide one additional year of follow up and include the effect on minimal residual disease and in clinically relevant subgroups. After 25.4 months of follow up, daratumumab plus lenalidomide/dexamethasone prolonged progression-free survival versus lenalidomide/dexamethasone alone (median not reached vs. 17.5 months;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
183
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 195 publications
(202 citation statements)
references
References 28 publications
11
183
0
4
Order By: Relevance
“…(14) The elotuzumab regimen also showed a slightly lower ORR (79%) than the current study, providing further support for the use of the carfilzomib plus lenalidomide and dexamethasone regimen. Interim data from a phase 3 study by Dimopoulos et al (15) showed a comparable ORR for the daratumumab plus lenalidomide and dexamethasone regimen (93%) to that observed in the current study.…”
Section: Discussionsupporting
confidence: 79%
“…(14) The elotuzumab regimen also showed a slightly lower ORR (79%) than the current study, providing further support for the use of the carfilzomib plus lenalidomide and dexamethasone regimen. Interim data from a phase 3 study by Dimopoulos et al (15) showed a comparable ORR for the daratumumab plus lenalidomide and dexamethasone regimen (93%) to that observed in the current study.…”
Section: Discussionsupporting
confidence: 79%
“…Likewise, the median PFS of 18·6 months with our RCD fixed‐dose nine‐cycle regimen was similar to that of 19·6 months obtained with continuous RD in patients at first relapse enrolled in the Pollux trial, that compared daratumumab plus lenalidomide plus dexamethasone versus lenalidomide plus dexamethasone (Dimopoulos et al , ). Likewise, in three other trials assessing continuous treatment with RD as control arm, the median PFS of this doublet ranged between 14·7 and 18·4 months (Lonial et al , ; Stewart et al , ; Moreau et al , ).…”
Section: Discussionsupporting
confidence: 76%
“…22,23 Subgroup analyses from the phase 3 ENDEAVOR study demonstrated that carfilzomib (20/56 mg/m 2 dosing schedule) plus 20 mg dexamethasone demonstrated encouraging activity in lenalidomide-refractory RRMM patients. 7,8 The favorable tolerability of triplet or quadruplet daratumumabbased regimens observed across studies in MM 6,[19][20][21]24,25 provided the rationale for evaluating the combination of daratumumab and weekly carfilzomib in the multiarm phase 1b study MMY1001. Here, we report the safety, pharmacokinetics, and preliminary efficacy of daratumumab plus carfilzomib and dexamethasone (D-Kd) in patients with RRMM, including lenalidomide-refractory patients.…”
Section: Introductionmentioning
confidence: 99%